2021
DOI: 10.1136/jitc-2021-003580
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, open-label, phase 2 study of andecaliximab plus nivolumab versus nivolumab alone in advanced gastric cancer identifies biomarkers associated with survival

Abstract: BackgroundMatrix metalloproteinase-9 (MMP9) selectively cleaves extracellular matrix proteins contributing to tumor growth and an immunosuppressive microenvironment. This study evaluated andecaliximab (ADX), an inhibitor of MMP9, in combination with nivolumab (NIVO), for the treatment of advanced gastric cancer.MethodsPhase 2, open-label, randomized multicenter study evaluating the efficacy, safety, and pharmacodynamics of ADX+NIVO versus NIVO in patients with pretreated metastatic gastric or gastroesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 77 publications
0
21
1
Order By: Relevance
“…Although the differentiated histological type is an advantage of AGC ( 52 ), this case was a poorly differentiated adenocarcinoma with a good response to nivolumab. Distinct from our case, previous studies have suggested that HER-2 -positive status is related to the improvement of prognosis ( 18 , 53 ). Furthermore, some studies have proposed that the co-expression of HER-2 and PD-L1 may contribute to the immune escape of GC, meaning that HER-2 -negative status creates favorable conditions for effective immunotherapy ( 12 ).…”
Section: Discussioncontrasting
confidence: 81%
“…Although the differentiated histological type is an advantage of AGC ( 52 ), this case was a poorly differentiated adenocarcinoma with a good response to nivolumab. Distinct from our case, previous studies have suggested that HER-2 -positive status is related to the improvement of prognosis ( 18 , 53 ). Furthermore, some studies have proposed that the co-expression of HER-2 and PD-L1 may contribute to the immune escape of GC, meaning that HER-2 -negative status creates favorable conditions for effective immunotherapy ( 12 ).…”
Section: Discussioncontrasting
confidence: 81%
“…For TGF-β, only four studies roughly met our inclusion criteria after screening title and abstracts. Two studies ( 60 , 61 ) investigated gene signatures of TGF-β rather than peripheral TGF-β concentration. One study ( 62 ) measured the peripheral level of TGF-β 1 week after anti-PD-1 immunotherapy, which did not meet our requirement.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may also be present and play a role in chronic diseases, including chronic stages of IBD and cancer. Along this line, it may be relevant to mention that recent oncology studies with Andecaliximab in cancer did not yield beneficial effects ( 75 , 76 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%